The Application of Demonstrated Learning Methods to Increase Primary School Students' Science Learning Results - Prananda, Gingga; Prihantini; Judijanto, Loso; Purwoko, Bambang; Stavinibelia; Lestari, Nana Citrawati; Efendi, Nofriza (Postgraduate, University of Mataram, 2023)
The paper aims to determine the difference in science learning outcomes of students who apply the demonstration method and the science learning outcomes of students who use conventional learning in class IV elementary school. The type of research that the author uses is experimental research. This research uses a group of research subjects from a certain population, then grouped randomly into two groups or classes, namely the experimental class and the control class. The experimental class was treated using the demonstration method and the control class used the conventional method, then both classes underwent the same post-test. The sampling technique used was non-probability sampling with proportional sampling. The same number of students and class average scores that are close to the same are class VA and class VB. After getting the sample class, the two classes were randomly drawn, then class VA was obtained as the experiment and class VB as the control. The results of this research can be seen from the results of the hypothesis test using the t-test which was carried out so that the value of t_count=0 and t_table= 2.02 was obtained. From the distributed table t, we get ttable = 2.02. So, it can be concluded that t_count > t_tabel, where 0 > 2.02, thus the working hypothesis H_1 is accepted, meaning there are significant differences in learning outcomes in the two samples. This research concluded that the science learning results of class IV students who used the demonstration learning method did not have a significant difference because the two sample classes got the same learning results, due to the limited time of the researcher who delivered the material to the experimental class